Improving Geldanamycin Production in Streptomyces geldanamycininus Through UV Mutagenesis of Protoplast - Yuan Yuan; Lu Yang; Zhikai Fang; Haimin Chen; Fei Sun; Hong Jiang; Jian Zhou (Microorganisms)
Geldanamycin, a benzoquinone ansa antibiotic, has been extensively applied in medical, agricultural, and health research areas due to its antitumor, antifungal, herbicidal, and antiradiation effects. In this study, an improvement of geldanamycin production by Streptomyces geldanamycininus FIM18-0592 was first performed by protoplasts combined with UV mutagenesis and ribosome engineering technology, respectively. The results showed that strains induced by UV mutagenesis of protoplasts were superior to protoplasts treated with erythromycin in terms of the positive variability, average relative titer, and maximum relative titer, with values of 51.95%, 99%, and 136%, respectively. A mutant strain that produced 3742 μg/mL geldanamycin was generated by protoplast UV mutagenesis, with a 36% higher yield than the initial strain. Multi-omic analysis revealed that the high-yielding geldanamycin in mutant strain 53 could upregulate GdmG and GdmX by 1.59 and 2.38 times in the ansamycin synthesis pathway, and downregulate pks12, pikAI, and pikAII by 0.25, 0.37, and 0.48 times in the fatty acid synthesis pathway, which was crucial for geldanamycin production. Our study provides a novel S. geldanamycininus geldanamycin production strategy and offers valuable insights for mutagenesis and breeding of other microorganisms.